2020
DOI: 10.1093/jamia/ocaa229
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ electronic inbox work patterns and factors associated with high inbox work duration

Abstract: Objectives Electronic health record systems are increasingly used to send messages to physicians, but research on physicians’ inbox use patterns is limited. This study’s aims were to (1) quantify the time primary care physicians (PCPs) spend managing inboxes; (2) describe daily patterns of inbox use; (3) investigate which types of messages consume the most time; and (4) identify factors associated with inbox work duration. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…Of this time, on average, approximately 33% of this time is spent on documentation, 13% on inbox activity, and 12% on orders ( Figure 2 ). 16 , 19 , 20 These values and proportions are consistent with previous literature 16 , 19 , 20 , 29 and can provide a benchmark for future measurement of standardized EHR use. Consistent with a case study from UCSF, 30 we found that female physicians spend more time on the EHR than their male colleagues, even after controlling for age, health system, medical specialty, and number of clinical hours scheduled.…”
Section: Discussionsupporting
confidence: 88%
“…Of this time, on average, approximately 33% of this time is spent on documentation, 13% on inbox activity, and 12% on orders ( Figure 2 ). 16 , 19 , 20 These values and proportions are consistent with previous literature 16 , 19 , 20 , 29 and can provide a benchmark for future measurement of standardized EHR use. Consistent with a case study from UCSF, 30 we found that female physicians spend more time on the EHR than their male colleagues, even after controlling for age, health system, medical specialty, and number of clinical hours scheduled.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies on EHR use patterns have quantified the time spent on different EHR activities within and outside of work hours [ 14 , 24 ]. However, variation among physicians is not well studied, and no previous study has attempted to characterize physicians based on their patterns of daily inbox use.…”
Section: Discussionmentioning
confidence: 99%
“…For EHR inbox management, a 2017 study [ 14 ] using EHR logs found that time spent in the inbox accounted for 24% of total EHR time, and of the time spent in the inbox, a larger proportion was spent after work hours compared with the time spent on other EHR activities. A study reported that 86% of surveyed physicians worked outside of work hours to respond to inbox messages [ 23 ], whereas another study reported that 37% of inbox work was done outside of work hours [ 24 ]. In addition to the time it takes within and outside of work hours, inbox-related burden has been attributed to the volume and source of EHR messages [ 5 , 7 ] and information overload from notifications (ie, asynchronous alerts) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we found that MyChart messaging comprised nearly half of all RCs. Although the convenience and availability of such messaging overall has facilitated provider–patient communication in the era of digital healthcare, the administrative burdens of responding to RCs may have also increased for providers, 22,23 novel solutions to reduce RC burden are needed. Recently, Common Procedural Terminology codes 99421‐3 were introduced by the American Medical Association 24,25 to allow providers to bill for patient‐initiated digital communications, including MyChart and secure email.…”
Section: Discussionmentioning
confidence: 99%